In-depth assessment of the public agricultural extension system of Ethiopia and recommendations for improvement - Davis, Kristin E.; Swanson, Burton; Amudavi, David; Mekonnen, Daniel Ayalew; Flohrs, Aaron; Riese, Jens; Lamb, Chloe; Zerfu, Elias (International Food Policy Research Institute, 2010)
Eighty-three percent of the population of Ethiopia depends directly on agriculture for their livelihoods, while many others depend on agriculture-related cottage industries such as textiles, leather, and food oil processing. Agriculture contributes about 46.3 percent of gross domestic product (GDP) (World Bank 2008) and up to 90 percent of total export earnings. As part of the current five-year (2006-2011) Plan for Accelerated and Sustained Development to End Poverty (PASDEP), the government is continuing to invest heavily in agriculture. A core part of the government's investment in agriculture is the public agricultural extension system. This study was conducted to assess the strengths and constraints of the public extension system and to provide suggestions on “best fit” solutions and their scale-up opportunities. The review used a variety of analytical tools to develop the overall findings, including extensive field visits to six of nine regions in Ethiopia; interviews with farmer trainees at farmer training centers (FTCs), more than 100 extension personnel, extension experts, nongovernmental organization (NGO) groups, and government representatives; and a literature review on Ethiopian extension. The study assessed strengths and constraints in the field-level extension system, the ATVET system, and the extension institutional environment. The researchers also considered the overall enabling environment within which extension operates. The field-level extension service has a strong foundation of FTCs and trained development agents (DAs) already in place in the field. Roughly 8,489 FTCs have been created throughout Ethiopia, and about 62,764 DAs have been trained in total, with a reported 45,812 staffed on location. Woreda (district) and regional offices are adequately staffed. DAs and woreda staff have strong technical skills and theoretical knowledge, and are generally trained as specialists. Pockets of entrepreneurialism and innovation exist in specific FTCs and woredas. While acknowledging these strengths, the researchers also identified several sets of constraints within the field-level extension system that will require attention. Basic infrastructure and resources at the FTC and woreda level remain a major constraint, particularly in relation to operating funds: the vast majority of FTCs and kebeles do not have operating equipment or inputs to pursue typical extension activities on the demonstration farm. There are major “soft” skill gaps for DAs and subject matter specialists (SMSs) in the FTCs and woredas, and their ability to serve farmers is limited given a lack of practical skills. Finally, the overall field-level system is often limited in its ability to meet farmer needs and demands; mechanisms to make it more farmer-driven and market-oriented would yield greater results. The authors employed a similar approach at the ATVET level to identify strengths and constraints. Strengths at the ATVET level include a strong record of training broad groups of DAs, a strong technical curriculum, and some pockets of innovation and practical training, including linkages to markets and farmers. Constraints include limited success in enabling DAs to gain practical experience, particularly related to their internships at the woreda level; limited linkages to the broader educational system and research system in Ethiopia; and a general lack of resources to effectively transmit the required skill set to DAs. The countrywide enabling environment in which extension operates is critical to extension efforts. Various aspects of the enabling environment were considered, including seed and other inputs, water management, and credit systems, as well as producer groups. Constraints were also assessed, leading to the conclusion that the enabling environment requires strengthening, particularly in the areas of seed and credit, if extension is to achieve its full potential impact.